Pengaruh Tingkat Pendidikan Orangtua dan Metode Pemberian Tugas Terhadap Motivasi Belajar Peserta Didik SDN Karangsembung 01 - Amanda Meiliawati; Laelia Nurpratiwiningsih; Dedi Romli Triputra (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to analyze the effect of parental education level and assignment method on students' learning motivation at SDN Karangsembung 01. This study uses the Ex-Post Facto type with saturated sampling, which is a sampling technique when all members of the population are used as samples. The type of research used in this research is quantitative research with a descriptive approach. The analysis technique uses a partial test (t test). ). (1) The results of the partial test (t test) obtained the value of t count Parents' Education Level (X1) > t table 2,209 > 2.0261; so that H0 is accepted, Ha is accepted, which means that there is an influence of the variable level of parental education on the learning motivation of students at SDN Karangsembung 01, Kec. Songgom, Brebes Regency. (2) The result of the t-count value of the assignment method (X2) > t table 3,295 > 2,061; so that H0 is rejected, Ha is accepted, which means that there is an influence of the Assignment Method variable on the Learning Motivation of Students at SDN Karangsembung 01, Kec. Songgom, Brebes Regency.